Analytical and experimental investigations on fluid flow and thermal characteristics of a plate-fin heat sink subject to a uniformly impinging jet - Do, Kyu Hyung; Kim, Tae Hoon; Kim, Sung Jin (International journal of heat and mass transfer, 2010)
In this paper, modified similarity solutions for velocity and temperature distributions in the heat sink subject to a uniformly impinging jet are presented. A heat sink is modeled as a fluid-saturated porous medium and a similarity transformation is employed. The Brinkman-extended Darcy equations for fluid flow and two-equation model for heat transfer are used as the governing equations. Specifically, a method for analytically determining the permeability and the interstitial heat transfer coefficient is presented. Experimental investigations are conducted to validate the proposed similarity solutions. From comparison of experimental and analytical results, the analytical results are shown to accurately predict the pressure drop and thermal resistance of the heat sink subject to the uniformly impinging jet.